Effects of breakfast cereals containing various amounts of beta-glucan fibers on plasma glucose and insulin responses in NIDDM subjects - Tappy, L; Gugolz, E; Wursch, P (Diabetes care, 1996)
Objective: To determine whether increasing doses (amounts) of beta-glucan present in an extruded breakfast cereal affect the glycemic and insulinemic responses in eight NIDDM subjects, compared with the same responses after a continental breakfast (bread, milk, cheese, ham). Research Design and Methods: Breakfast cereals were produced using various proportions of oat bran enriched in fiber, which contain an unusually high amount of a viscous polysaccharide, called beta-glucan, and oat bran. The carbohydrate load was 35 g. Results: The maximum increases observed in plasma glucose after the breakfast cereal were 67% (P < 0.05), 42% (P < 0.001), and 38% (P < 0.001) with 4.0, 6.0, and 8.4 g beta-glucan, respectively, compared with the continental breakfast. There was a linear inverse relationship between dose of beta-glucan and plasma glucose peak or area under the glucose curve (R2 = 0.94, P < 0.05). Postprandial insulin increase was only 59-67% (P < 0.01) as high as the continental breakfast after all three levels of beta-glucan. Conclusions: The 50% decrease in glycemic response that was observed after the ingestion of 35 g carbohydrate is estimated to occur with approximately 5 g beta-glucan. This dose of beta-glucan can easily be attained without the loss of taste by incorporating oat bran concentrate in products.